FAKTOR RISIKO KEJADIAN NYERI PUNGGUNG BAWAH PADA SOPIR OJEK ONLINE MOBIL - Arinta Puspita Wati; Dennis Adi Purnama; Maria Belladonna Rahmawati; Trianggoro Budisulistyo (NEURONA, 2021)
Introduction: Low back pain (LBP) is one of the musculoskeletal problems that lead to disability, decreased productivity, and quality of life that usually happens among workers, employees, or drivers. An increase in demand using online car taxi services may lead to LBP. Aim: This preliminary study aims to determine the risk factors for LBP in online car taxi drivers. Methods: This observational analytic study was conducted using a cross-sectional design towards online car taxi drivers aged 25-64 years old in Semarang, with a minimal sample (n=15) calculated by the Lemeshow equation. The inclusion criteria for the sample in this study, i.e. online car-male taxi drivers who experience LBP, while the exclusion criteria were history of lumbar trauma or musculoskeletal disease. Data were taken by primary data, the Modified Oswestry Disability Index (MODI) questionnaire, and the numerical rating scale (NRS); then, the data were analyzed using Chi-square and logistic regression test. Results: Crosstabs showed an association of LBP with a period of working (p=0.011) and pain disability (p=0.017). At the same time, body mass index (BMI), physical activities, and exercise habits (p=0.231, p=0.168, and p=0.462, respectively) had no significant result on LBP in online car taxi drivers. Discussion: Risk factors for LBP in online car taxi drivers were a period of working and pain disability. Risk factors of BMI, physical activities, and exercise habits were not statistically significant.